Economics for administrators - Mongia, J. N. (New Delhi, 1982)
This book marks the first and pioneer attempt in providing a reference-book of Economics to Administrators. Economics is a vast and a dynamic subject. Any attempt to explore the whole territory of Economics, with so fragile a vehicle as a small book, would be almost ludicrous. Hence, while its apparent range is wide, it makes no claim to touch more than certain aspects of this field. The beginner will do well to skip some of the technical discussions but the remainder of the book is quite understandable to those without any formal training in economic theory Thus, care has been taken to avoid too much of technical preoccupation of pro fessional economists so far as the scope of the book has allowed and to make the material accessible to the wider circle of those who have a lively sense of the intimate relation between economic theory and practice in the world of today and have little time for what is merely "light-bearing", without also being "fruit bearing." The approach in this book follows the trend of modern economic thought which runs along aggregative lines and this is the justification for taking a 'macro' approach. The chief object of this book is to kindle interest in the fundamental problems of Economics and to point out the implications of certain economic facts.
Keywords: Economics